SURABAYA SINGLE WINDOW SEBAGAI BENTUK INOVASI PELAYAN PERIZINAN DI KOTA URABAYA - Isro' Lailia (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2020)
Fast and effective public services are a supporter of public administration so that continuous innovation is needed to improve the quality of public services. The city of Surabaya as one of the cities with the title of smart city has tried to always make innovations in an effort to improve the quality of public services, one of which is through the Surabaya Single Window. Surabaya Single Window is an online-based licensing service created to create effective public services. This article attempts to describe how the licensing service innovation carried out by the City Government of Suraya through the Surabaya Single Window covers five important aspects. The method used is descriptive qualitative using secondary data. It was found that the City of Surabaya succeeded in creating public service innovations through the Surabaya Single Window. The Surabaya Single Window has a positive impact on licensing services in the City of Surabaya, although in its implementation there are still certain guarantees.